2021
DOI: 10.4274/jtgga.galenos.2021.2020.0232
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for flow velocities and the indices of the ductus venosus in low-risk pregnancies

Abstract: Objective: Ductus venosus blood flow velocity measurements are mandatory in many clinical indications. The evaluation of the flow is performed either by comparing results with general reference tables or by qualitative assessment of the “a” flow, in regard to reversed or absent flow in the spectral waveforms. The aim was to develop normal reference ranges in low-risk pregnancies in our population. Material and Methods: Measurements of flow velocities (S, v, D, a) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(65 reference statements)
2
3
0
Order By: Relevance
“…Our results show a non-significant decrease in DVRI over the gestation period, in agreement with every other study. [ 23 33 39 42 ] As well, the reference values found in this study resembled those estimated by previous studies. Unexpected findings regarding this index were significant negative coefficients for the 5 th and 95 th percentile regression lines across the CRL range.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results show a non-significant decrease in DVRI over the gestation period, in agreement with every other study. [ 23 33 39 42 ] As well, the reference values found in this study resembled those estimated by previous studies. Unexpected findings regarding this index were significant negative coefficients for the 5 th and 95 th percentile regression lines across the CRL range.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier studies have demonstrated nonsignificant changes within this index during the first trimester of pregnancy. [ 22 23 33 39 ] Our estimated reference ranges were much close to previous reports, a bit narrower than those of Turan et al . [ 22 ]…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In GDM fetuses with septal hypertrophy, increased right atrial pressure is associated with right ventricular dysfunction (22). DV blood flow spectrum showed a decreased flow velocity and an increased DV-PI in GDM fetuses (23,24).…”
Section: Discussionmentioning
confidence: 93%